2017
DOI: 10.1007/s10147-017-1133-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of diclofenac and celecoxib with an opioid yields superior efficacy in metastatic bone cancer pain: a randomized controlled trial

Abstract: Although limited by the relatively small samples, these results indicate that using two NSAIDs along with an opioid in treating metastatic bone cancer pain was more effective and acceptable, which is worthy of further clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Administration of NSAIDs, acetaminophen, or steroids may improve bone pain control when combined with opioid analgesics. [220][221][222] Topical diclofenac, including gel or patch, may provide relief for pain due to bone metastases with minimal system effects. 220 Although bone-modifying agents such as bisphosphonates and RANKL (receptor activator of nuclear factorkappa-B ligand) inhibitors are primarily used for the reduction of overall SREs, clinical trials have established that these agents can have an analgesic effect on patients with metastatic bone pain from a variety of tumors.…”
Section: Management Of Bone Pain Without An Oncologic Emergencymentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of NSAIDs, acetaminophen, or steroids may improve bone pain control when combined with opioid analgesics. [220][221][222] Topical diclofenac, including gel or patch, may provide relief for pain due to bone metastases with minimal system effects. 220 Although bone-modifying agents such as bisphosphonates and RANKL (receptor activator of nuclear factorkappa-B ligand) inhibitors are primarily used for the reduction of overall SREs, clinical trials have established that these agents can have an analgesic effect on patients with metastatic bone pain from a variety of tumors.…”
Section: Management Of Bone Pain Without An Oncologic Emergencymentioning
confidence: 99%
“…[220][221][222] Topical diclofenac, including gel or patch, may provide relief for pain due to bone metastases with minimal system effects. 220 Although bone-modifying agents such as bisphosphonates and RANKL (receptor activator of nuclear factorkappa-B ligand) inhibitors are primarily used for the reduction of overall SREs, clinical trials have established that these agents can have an analgesic effect on patients with metastatic bone pain from a variety of tumors. Clinical trials have demonstrated the palliative effects of bisphosphonates (eg, zoledronic acid, ibandronate) [223][224][225][226][227] and denosumab (a RANKL inhibitor) 225,228 on pain related to bone metastases.…”
Section: Management Of Bone Pain Without An Oncologic Emergencymentioning
confidence: 99%
“…One phase II trial (21), six randomized controlled trials (22)(23)(24)(25)(26)(27) and three other prospective series (28)(29)(30) were included in this review. The randomized controlled trials were double-blinded in four trials (24-27) (of which one was placebo-controlled) and open label in two (22,23). Three studies were single-arm (21, 28, 29) six were 2-arm (22,(24)(25)(26)(27)30) and one 3-arm (23).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Four studies included only patients with NSCLC, with a minimum of one bone metastasis (21,22,28,30). The other studies included also patients with CIBP caused by bone metastases of solid malignancies (256 out of 978 patients in total had NSCLC) (23)(24)(25)(26)(27)29). The number of patients with NSCLC enrolled in the studies ranged from 14 (24,28) to 144 (30), leading to in total 554 patients with NSCLC included in this review.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…В ряде случаев (при умеренно выраженной боли) они могут использоваться в виде монотерапии, но наиболее часто их применяют в комплексе с опиоидными анальгетиками. По данным РКИ [62][63][64][65][66] и соответствующего метаанализа (включавшего данные 42 РКИ; n=3084) [67], при онкологической боли НПВП достоверно превосходят плацебо. В недавно опубликованном метаанализе 11 РКИ различного типа, включая открытые (n=949), было показано снижение боли с высокой до умеренной у 26-51% больных, получавших НПВП [68].…”
Section: эффек тивность нестероидных противовоспалительных препаратовunclassified